THE IMPACT OF VIRTUAL CLASSROOMS ON SPEAKING ANXIETY - Shuhratova Mavluda Shamshodovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: In recent years, the landscape of education has undergone a significant transformation due to the advancement of technology and the widespread adoption of virtual classrooms. The shift from traditional, face-to-face classrooms to online learning environments has led to several changes in the ways students interact, communicate, and learn. One of the most impactful areas that has garnered the attention of researchers and educators alike is the effect virtual classrooms have on speaking anxiety among students. Speaking anxiety, often described as feelings of nervousness, worry, or fear associated with speaking in front of others, can hinder academic performance and personal development. Understanding the nuanced impact of virtual classrooms on this aspect is crucial for optimizing the online learning experience and supporting students in their educational journeys.